Perception of personal financial planning in the life insurance industry of Singapore. - Chan, Jin Ming. (2008)
This study focuses on examining their knowledge on personal financial planning, the roles expected of a financial planner, their conflict of interests in providing this service, as well as their personal feedback on financial planning.